Autoimmune Pancreatitis and Pancreatic Cancer. Is there a Relationship between these Conditions? About a Case and Review of the Literature - Durango Hernández, D. J.; Damacio Breton, Roberto Elías; Lopez Bernal, Carlos Alberto; Grageda Flores, Edgar; Alonso Blanco, Miguel Angel; Ledesma Lujan, Aldo Santiago (British Journal of Healthcare and Medical Research, 2024)
Introduction: Chronic pancreatitis is a risk factor for pancreatic cancer, but the association with autoimmune pancreatitis (AIP) is less clear. AIP is a rare disease with a challenging diagnosis. Two types of AIP are presented: type 1 and type 2. Case Presentation: A 35-year-old female with a history of pancreatitis and subsequent diagnosis of pancreatic cancer. Discussion: AIP can be difficult to diagnose because it shares characteristics with pancreatic cancer. IgG4 levels can help diagnose AIP, but they are not always elevated. There is a possible association between AIP and pancreatic cancer, especially in type 1 AIP. Treatment of AIP with steroids can improve symptoms. Conclusions: AIP should be considered in the differential diagnosis of patients with obstructive jaundice and pancreatic lesions. Pancreatic biopsy is necessary for a definitive diagnosis of AIP.